N-acetyltransferase 10 regulates alphavirus replication via N4-acetylcytidine (ac4C) modiﬁcation of the lymphocyte antigen six family member E (LY6E) mRNA - Yamei Dang; Jia Li; Yuchang Li; Yuan Wang; Yajing Zhao; Ningbo Zhao; Wanying Li; Hui Zhang; Chuantao Ye; Hongwei Ma; Liang Zhang; He Liu; et al. (2024)
ABSTRACT Epitranscriptomic RNA modifications can regulate the stability of mRNA and affect cellular and viral RNA functions. The N4-acetylcytidine (ac4C) modification in the RNA viral genome was recently found to promote viral replication; however, the mechanism by which RNA acetylation in the host mRNA regulates viral replication remains unclear. To help elucidate this mechanism, the roles of N-acetyltransferase 10 (NAT10) and ac4C during the infection and replication processes of the alphavirus, Sindbis virus (SINV), were investigated. Cellular NAT10 was upregulated, and ac4C modifications were promoted after alphavirus infection, while the loss of NAT10 or inhibition of its N-acetyltransferase activity reduced alphavirus replication. The NAT10 enhanced alphavirus replication as it helped to maintain the stability of lymphocyte antigen six family member E mRNA, which is a multifunctional interferon-stimulated gene that promotes alphavirus replication. The ac4C modification was thus found to have a non-conventional role in the virus life cycle through regulating host mRNA stability instead of viral mRNA, and its inhibition could be a potential target in the development of new alphavirus antivirals. IMPORTANCE The role of N4-acetylcytidine (ac4C) modification in host mRNA and virus replication is not yet fully understood. In this study, the role of ac4C in the regulation of Sindbis virus (SINV), a prototype alphavirus infection, was investigated. SINV infection results in increased levels of N-acetyltransferase 10 (NAT10) and increases the ac4C modification level of cellular RNA. The NAT10 was found to positively regulate SINV infection in an N-acetyltransferase activity-dependent manner. Mechanistically, the NAT10 modifies lymphocyte antigen six family member E (LY6E) mRNA—the ac4C modification site within the 3′-untranslated region (UTR) of LY6E mRNA, which is essential for its translation and stability. The findings of this study demonstrate that NAT10 regulated mRNA stability and translation efficiency not only through the 5′-UTR or coding sequence but also via the 3′-UTR region. The ac4C modification of host mRNA stability instead of viral mRNA impacting the viral life cycle was thus identified, indicating that the inhibition of ac4C could be a potential target when developing alphavirus antivirals.